Heritage of Vavilov N.I. in modern science and practical breeding (In commemoration of the 125-th anniversary of Vavilov N.I.) - S.K. Temirbekova; I.M. Kulikov; E.F. Ionov; O.G. Kasakov; N.E. Ionova; A.A. Kurilo (Овощи России, 2012)
The significance of world germplasm collection of vegetable crops and their wild relatives developed by Vavilov N.I. for scientific and breeding purposes are undertaken in the article.